2020
DOI: 10.3390/antibiotics9050220
|View full text |Cite
|
Sign up to set email alerts
|

High-Value Plant Species Used for the Treatment of “Fever” by the Karen Hill Tribe People

Abstract: The symptom "fever" is generally not itself a terminal condition. However, it does occur with common mild to severe ailments afflicting the world population. Several allopathic medicines are available to attenuate fever by targeting the pathogen or the symptom itself. However, many people in marginal civilizations are obligated to use locally grown medicinal plants due to limited access to common pharmaceuticals. The Karen ethnic group is the biggest ethnic minority group in the hill-tribes of Thailand. They u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…These are common symptoms that people experience every year, especially seasonal symptoms such as fever, cough, headache, and sore throat. A previous study showed that Thai Karen had tremendous knowledge of medicinal uses for treatments of fever ( Phumthum and Sadgrove, 2020 ). Diarrhea is usually found among Thai rural population because of the consumption of unsanitary or very sour and spicy food, and body aches and pains are commonly found among laborers.…”
Section: Discussionmentioning
confidence: 99%
“…These are common symptoms that people experience every year, especially seasonal symptoms such as fever, cough, headache, and sore throat. A previous study showed that Thai Karen had tremendous knowledge of medicinal uses for treatments of fever ( Phumthum and Sadgrove, 2020 ). Diarrhea is usually found among Thai rural population because of the consumption of unsanitary or very sour and spicy food, and body aches and pains are commonly found among laborers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ]. For the treatment of sickness, the Karen depends on a large body of traditional knowledge about medicinal plants, especially herbs for the treatment of stomachaches, diarrhea, coughs, fevers, infectious diseases, and also plants for tonic and refreshment [ 14 , 18 , 19 , 20 ]. Therefore, the Karen hold a vast amount of medicinal plant knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the unique anti-malarial effects of V. doniana extracts from the specimen collected in the current study could be attributed to symptom treatment, rather than targeting of the pathogen itself. In this regard, many ‘anti-fever’ species in ethnomedicine confer their effects by anti-inflammatory activity following COX-2 inhibition [ 21 ], which reduces prostaglandin E(2) levels in the hypothalamus and attenuates the effects of pyrogens secreted by the invading pathogen [ 22 ]. In this regard, the Kenyan study of V. doniana [ 5 ] demonstrated that the ecdysteroids confer significant in vivo anti-inflammatory effects at 100 mg.kg −1 (b.w., PO) in a Sprague Dawley rat model, by oral administration.…”
Section: Resultsmentioning
confidence: 99%